Caracterização de um detector tipo Long Counter como padrão secundário para medição de fluência de nêutrons - Fernandes, Simone da Silva (2019)
This work describes the steps for the characterization of a Long Counter neutron detector that is traditionally used as a secondary standard for neutron fluence measurement. The experimental methodology of characterization of this device was performed at facilities of the Ionizing Radiation Metrology National Laboratory (LNMRI/ IRD) and reproduced by MCNPX code computer simulation with ( 252Cf(D2O), 252Cf e 241 Am-Be) reference sources cited in ABNT NBR ISO 8529 and in addition to the 131Pu-Be source. The Long Counter was submitted to the evaluation tests of the effective centre, corrections for scattering influence, sources anisotropy, evaluation of directional dependence and evaluation of the response with and without the cadmium shield. After investigation, the neutron fluence results were compared with measurements performed of primary system Manganese Sulfate Bath, presented excellent agreement within the uncertainties less than 2%. The response function with 84 energy range is flat in the range 1eV-10MeV. Two fields were characterized with the Long Counter, the thermal neutrons of the FT2 system at LNMRI facilities, and the fast neutrons with the 14.1MeV generator at IEAv/CTA facilities, determining the corresponding values for the operational quantities H * (10) and Hp (10).